The Impact of Digital Platform Implementation on Operational Effectiveness & the Moderating Role of Strategic Partnership Quality: A Case Study of the Neutrafix Platform at PT Telin - Rahmad Fitriyanto; Anton M Azis; Irayanti Adriant (Return : Study of Management, Economic and Bussines, 2026)
This study analyzes the influence of the implementation of digital platforms on operational effectiveness with the role of moderating the quality of strategic partnerships, using a case study of the Neutrafix Platform at PT Telin. Departing from the gap in the literature dominated by internal factors and perceptual survey methods, this study shifts the focus to external-relational factors and integrates Transaction Cost Economics Theory and Relational View. The study used an explanatory quantitative approach with a single case study design. PT Telin's time-series secondary data for the period January 2021–December 2025 (60 monthly data points) is processed into three measurable variables: Digital Platform Implementation (X) with Software Quality Score, Strategic Partnership Quality (Z) with Strategic Factor Score, and Operational Effectiveness (Y) as a composite index (cost, speed, reliability, service quality). Data analysis using Moderated Regression Analysis (MRA) with SPSS. The results of the study show that the Implementation of Digital Platform has a positive and significant effect on Operational Effectiveness (H1 accepted). On the other hand, the Quality of Strategic Partnerships has a significant effect but with a negative direction (H2 accepted, negative coefficient), and has been shown to moderate the relationship between digital platforms and operational effectiveness in a negative direction (H3 accepted), which indicates that partnerships actually weaken the positive impact of technology. The discussion revealed that the counter-intuitive findings were explained by the concept of relational inertia from the dynamic version of the Relational View and the partnership life cycle theory. The stagnation of the partnership score over five years indicates a prolonged maturity phase , in which coordination and complacency costs lead to a decline in the partnership's contribution to operational performance. The study concludes that digital platforms are a key driver of operational effectiveness, but their benefits can be eroded by stagnant partnerships that are not dynamically managed. Practical advice for PT Telin's management includes periodic partnership evaluations, performance-based contracts, multi-sourcing, and redesign of coordination mechanisms. Theoretically, this study contributes to the strategic management literature by showing that the moderation effects of partnerships are not always positive in the long run.